Apolipoprotein B and non-high-density lipoprotein cholesterol reveal a high atherogenicity in individuals with type 2 diabetes and controlled low-density lipoprotein-cholesterol - Fonseca, Liliana (2020)
Background: Lipid-lowering therapy is guided by Low-density-lipoprotein cholesterol (LDL-c) levels, although the cardiovascular disease (CVD) risk could be better reflected by other lipid parameters. This study aimed at comparing a comprehensive lipid profile between patients with type 2 diabetes mellitus (T2DM) with LDL-c concentration within and above target. Methods: A comprehensive lipid profile was characterized in 96 T2DM patients. The European Society of Cardiology/European Atherosclerosis Society (ESC/EAS) 2016 and 2019 Guidelines for the Management of Dyslipidemias were used to define LDL-c targets. Results: In this population, only 28.1 and 16.7% of patients had mean LDL-c levels within target, as defined by the 2016 and 2019 guidelines, respectively. Applying the 2016 guidelines criteria, in patients with LDL-c within target, 22, 25 and 44% presented non-high-density lipoprotein cholesterol (non-HDL-c), Apolipoprotein B (ApoB) and oxidized LDL-c levels above the recommended range, respectively, whereas according to the 2019 guidelines criteria, 50, 39 and 44% of the patients with LDL-c within target had elevated high-density lipoprotein cholesterol (HDL-c), ApoB and oxidized LDL-c levels, respectively. LDL-c was strongly correlated with non-HDL-c (r = 0.850), ApoB (r = 0.656) and oxidized LDL-c (r = 0.508). Similarly, there was a strong correlation between non-HDL-c with both ApoB (r = 0.808) and oxidized LDL-c (r = 0.588). Conclusions: These findings emphasize the limitations of only considering LDL-c concentration for cardiovascular (CV) risk assessment. Targeting only LDL-c could result in missed opportunities for CV risk reduction in T2DM patients. These data suggest that non-HDL-c, ApoB and oxidized LDL-c levels could be considered as an important part of these patients' evaluation allowing for a more accurate estimation of CV risk and hopefully better management of these high-risk patients.